Pengaruh Pendidikan Kesehatan Dengan Media Booklet Terhadap Kecemasan - dian, dian_therezah_yadi; Suzanna; Ayu Dekawaty (Institut Citra Internasional, 2025)
Anxiety is a condition where someone feels uncomfortable accompanied by shadows of fear, alienation, accompanied by a sense of insecurity. Conditions of fear and uncertainty can convey a response to a situation where someone can predict a threatening situation so that someone can prepare themselves to face the situation. The purpose of this study was to determine the effect of health education using booklet media on client anxiety at the Muratara Palembang Shelter. The research design in this study was Pre-Experimental Pretest-Post Test Only One Group Design with a sample of 35 respondents. Results From the study it was found that health education using